ENGLISH TEACHERS’ ABILITY IN IDENTIFYING AND PRODUCING ACADEMIC TEXTS: A GENRE-BASED CASE STUDY IN SRAGEN - Djatmika Djatmika, M.A.; Riyadi Santosa; Tri Wiratno; Rara Sugiarti; Agus Hari Wibowo (Prasasti: Journal of Linguistics)
This research was conducted to examine the ability of English teachers of senior high schools in Sragen Regency in identifying and producing texts with various types of genres that are needed to be developed into teaching materials. Members of High School English Teachers Association in the regency were involved in the research. An instrument in the form of test was distributed to all the members of the association measuring their capability in identifying various of texts, in producing them, as well as in using them in composing a journal article. The responses given by the teachers show that they actually do not have good knowledge and language skills in identifying as well as producing texts in certain types. Furthermore, they also got problems in positioning what type of text to which part of a journal article. This condition indicates that the teachers still need upgrading program for their language skills to compose a journal article, and in addition they need others to give a hand during the process of article writing.